2021
DOI: 10.35706/acc.v6i02.5616
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Komite Audit dan Struktur Modal terhadap Pengungkapan Sustainability Report

Abstract: Penelitian ini bertujuan untuk menganalisis dan mendapatkan bukti empiris pengaruh komite audit dan struktur modal terhadap pengungkapan sustainability report pada perusahaan yang mengikuti Asia Sustainability Reporting Rating periode 2015-2020. Penelitian ini merupakan penelitian kuantitatif dengan metode deskriptif, data yang digunakan merupakan data sekunder dan kemudian dilakukan pengujian dan mendeskripsikan atau memberikan gambaran atas hasil tersebut. Populasi yang digunakan dalam penelitian ini m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…The association between capital structure and sustainability disclosure Based on the hypothesis test, the capital structure is not associated with sustainability disclosure. This result is in line with Afifulhaq (2018), Aini & Subardjo (2018), Ainiyah & Sinta (2019), Krisyadi & Elleen (2020), Privika et al (2021), Riza (2017), but it is not in line with (Kusumawati & Fauziah, 2020;Liana, 2019;Wulandari et al, 2021). Differences related to this study's results may be caused by differences in research samples, data analysis methods, research periods, and proxies used in measuring the variables used.…”
Section: Resultsmentioning
confidence: 41%
See 3 more Smart Citations
“…The association between capital structure and sustainability disclosure Based on the hypothesis test, the capital structure is not associated with sustainability disclosure. This result is in line with Afifulhaq (2018), Aini & Subardjo (2018), Ainiyah & Sinta (2019), Krisyadi & Elleen (2020), Privika et al (2021), Riza (2017), but it is not in line with (Kusumawati & Fauziah, 2020;Liana, 2019;Wulandari et al, 2021). Differences related to this study's results may be caused by differences in research samples, data analysis methods, research periods, and proxies used in measuring the variables used.…”
Section: Resultsmentioning
confidence: 41%
“…Study Kusumawati & Fauziah (2020), Liana (2019) and Wulandari et al (2021) found that capital structure decreases the sustainability disclosure. The size of the capital structure shows the increasing number of stakeholders involved in the implementation of sustainability carried out by the company, including creditors.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Penelitian sebelumnya yang telah menguji nilai perusahaan dilakukan dengan ukuran perusahaan (D. K. Sari & Wahidahwati, 2021;Vernando & Erawati, 2020), pertumbuhan penjualan (Apriliyanti et al, 2019;Suwardika & Mustanda, 2017), profitabilitas (Apriliyanti et al, 2019;Bhimantara & Dinarjito, 2021;Hertina et al, 2019;N. A. Sari & Susilowati, 2021), likuiditas perusahaan (Nasrun & Suyatmin, 2020;Sugiyanto & Setiawan, 2019), kebijakan dividen (Bahrun et al, 2020;Salman et al, 2020), kebijakan utang (Apriliyanti et al, 2019;Carolina et al, 2020;Firmansyah, Setiawan, et al, 2020;Hertina et al, 2019;Nasrun & Suyatmin, 2020;Suripto, 2019;Wulandari et al, 2021), keputusan investasi (Bahrun et al, 2020), revaluasi aset (Salman et al, 2020), kepemilikan instrumen derivatif (Firmansyah & Purnama, 2020;Novianti & Firmansyah, 2020), modal intelektual (Gaol et al, 2021;Josephine et al, 2019), kepemilikan manajerial (Widyaningsih, 2018), kepemilikan institusional (Toly et al, 2019;Widyaningsih, 2018), jumlah dewan direksi (Toly et al, 2019;Utomo & Dianawati, 2017), komisaris independen (Aryanto & Setyorini, 2019;Widyaningsih, 2018), dan komite audit (Aryanto & Setyorini, 2019;Utomo & Dianawati, 2017;Widyaningsih, 2018), pengungkapan tata kelola perusahaan (Damayanti & Firmansyah, 2021;…”
unclassified